Pembelajaran PAKBP dengan Metode PJBL Sebagai Upaya Peningkatan Kemandirian Fase C kelas 6 SD Katolik Karya Yosef Pontianak - Gontramus Jhon Ariyo Putra; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to enhance the independence of students in Catholic Religious Education and Character Education (PAKBP) through the implementation of the Project-Based Learning (PJBL) method in the 6th grade of SD Katolik Karya Yosef Pontianak. This research is based on the low level of student independence in completing tasks during lecture-based teaching. This Classroom Action Research was conducted in two cycles, with each cycle consisting of planning, action implementation, observation, and reflection stages. The research subjects were 30 6th-grade students in Phase C. Data collection instruments included observation, an independence questionnaire, and field notes. The indicators of independence observation covered students' ability to manage study time independently, complete tasks without teacher assistance, make appropriate decisions during the learning process, take initiative in seeking additional information, and take responsibility for assigned tasks. The results showed that the application of the PJBL method significantly increased student independence in PAKBP learning and academic achievement. Improvement was observed in students' ability to manage time, take initiative in completing projects, and make decisions during the learning process. In the first cycle, independence increased from 65% to 80%, while academic achievement in the proficient category rose from 70% to 85%, and in the competent category from 60% to 75%. Therefore, it can be concluded that PJBL, focusing on the independence dimension, can enhance both student independence and learning outcomes. It is recommended that PJBL be considered an effective approach to improving student independence and learning outcomes in PAKBP. The implication of this research is the importance of broader integration of the PJBL method in learning activities to support the development of students' character and abilities.